Skim, dive, surface : teaching digital reading - Cohn, Jenae (Teaching and learning in higher education (West Virginia University Press), 2021)
"Skim, Dive, Surface offers an invitation to focus not on losses to student learning but on the spectrum of affordances available within digital learning environments. It is designed to help college instructors across the curriculum teach digital reading in their classes, whether they teach face-to-face, fully online, or somewhere in between. Placing research from cognitive psychology, neuroscience, learning science, and composition in dialogue with insight from the scholarship of teaching and learning, Jenae Cohn shows how teachers can better frame, scaffold, and implement effective digital reading assignments. She positions digital reading as part of a cluster of literacies that students should develop in order to communicate effectively in a digital environment"--